Effects of Aqueous Stem Bark Extract of Cissus Populnea on Serum Lipid Profile in Normal and Diabetic Induced Rats - Geidam, Matawalli Ajagana (International Journal of Scientific Research and Management (IJSRM), 2015)
The study form four weeks experimental protocol involving intragastric administration of 100mg/Kg body weight of aqueous stem bark extract of Cissus populnea in normal and alloxan induced diabetic albino rats. In the diabetes induced group there is a significant increase (P